Extrinsic Motivation and Organizational Commitment : A Literarure Review - Zulkifli Musannip Efendi Siregar (Garuda Prestasi Nusantara Consulting, 2022)
Increasing employee commitment at work is one of the most important points for the company. Without organizational commitment from an employee, the employee will tend to work less than optimally. This study aims to find the answers to the research question of whether extrinsic motivation influence organizational commitment. Metode penelitian yang digunakan dalam penelitian ini adalah article review dari beberapa jurnal yang telah publish. The results of the study proved that extrinsic motivation influence organizational commitment. The results of this research have implications for policymakers, that employee must be given support and aslo increasing the employee extrinsic motivation such as providing fair promotion, reward, and also providing a good income. The limitations of this study are that the variables used as independent variables to test commitments are still few. In the future, it will be expected to increase variables and conduct research empirically. Keywords: Extrinsic Motivation; Organizational Commitment